Investigation into the Potential of Bio-based Automotive Engine Lubrication Oil Using Tribological Test Method - Mohamad Firdaus Bin Ayob, Mohamad Firdaus (Universiti Teknologi Petronas, 2008)

(untitled)
The objectives of this research are to analyse the bio-based lubrication behaviour using the tribological testing procedure, to evaluate the potential of its technical capability as a bio-based lubrication and to compare its properties to the existing commercial mineral lubrication and lastly conclude the findings of the study.